The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.3390/su14052933
|View full text |Cite
|
Sign up to set email alerts
|

Response Surface Method to Calculate Energy Savings Associated with Thermal Comfort Improvement in Buildings

Abstract: In developed countries, a large part of the building stock in 2050 will consist of currently existing buildings. Consequently, in order to achieve the objectives in terms of energy efficiency in the building sector we must consider not only new infrastructures but also the old ones. A reduction in energy consumption for climate control of between 50 and 90% can be achieved by rehabilitation and the implementation of different energy efficiency measures. Currently, these measures to reduce energy consumption an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 35 publications
(32 reference statements)
0
6
0
Order By: Relevance
“…Both floor and orientation factors should be included in future studies. The importance of occupants' activity regarding energy consumption in residential buildings may be an important factor [48,49] that was also neglected in this and previous studies using RSM in both residential and non-residential buildings [15][16][17][18][19][20][21]. It is therefore necessary to include the factors related to occupant activity for a more accurate analysis.…”
Section: Discussionmentioning
confidence: 98%
See 4 more Smart Citations
“…Both floor and orientation factors should be included in future studies. The importance of occupants' activity regarding energy consumption in residential buildings may be an important factor [48,49] that was also neglected in this and previous studies using RSM in both residential and non-residential buildings [15][16][17][18][19][20][21]. It is therefore necessary to include the factors related to occupant activity for a more accurate analysis.…”
Section: Discussionmentioning
confidence: 98%
“…In this paper, four design factors are selected that affect the building energy consumption, based on data extrapolated from the national TABULA project [9]. Compared to the previous studies utilizing RSM [15][16][17][18][19][20][21] for both residential and non-residential buildings, the inclusion of the overall heating and cooling system efficiency as a design factor is a novelty. It was shown that for both climate regions in Bosnia and Herzegovina (North and South) the cooling system efficiency had the strongest influence on the energy consumption for cooling when compared to the impact of SHGC, heat transfer coefficient of external walls, and roofs, while the heating systems efficiency had the second highest impact on the energy consumption for heating among the four design parameters selected.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations